Nanoemulsion-based delivery systems for curcumin: effect of carrier oil type on bioaccessibility and cell viability - Vicente, A. A. (2017)
Curcumin exerts a wide range of biological and pharmacological activities (e.g. anti-inflammatory and anticancer), however, its health benefits are limited by its poor solubility in aqueous media and low bioavailability. Nanoemulsions (NE) are particularly effective carriers for incorporating lipophilic bioactive compounds into many foods, improving their bioavailability and stability. The knowledge of NE and bioactive compounds behaviour during digestion/absorption is of utmost importance to assess their safety and to produce NE with optimized bioactivity. The purpose of this research was to evaluate the behaviour of curcumin NE formulated with two different carrier oils - long chain triglycerides (LCT) and medium chain triglycerides (MCT) - when submitted to an in vitro digestion. NE physicochemical properties (size, zeta-potential and morphology), free fatty acids release and curcumin bioaccessibility were evaluated. The impact of both formulations on Caco-2 cell viability was analyzed by MTT assay. In vitro digestion results indicated that both NE were only stable at mouth conditions, once they exhibited an increase in particle size from this stage on. Curcumin bioaccessibility increased 12 times when encapsulated in NE-MCT, compared with free curcumin. However, a low curcumin bioaccessibility was obtained for NE-LCT, and no significant differences were observed between NE-LCT and free curcumin. Overall, cell viability results demonstrated that curcumin encapsulated in NE-MCT and NE-LCT present no cytotoxic effects at curcumin concentrations lower than 20 and 25 g.mL-1, respectively. This work contributes to the development of NE with improved bioavailability and on their application in food sector by gathering fundamental data on digestion and safety of different NE.